Integration of Shangshan culture into the STEAM curriculum and teaching: results of an interview-based study - Qian, Chen; Ye, Jian-Hong; Zheng, Chaocan (Frontiers in Psychology, 2023)
Introduction Interdisciplinary science, technology, engineering, arts, and mathematics (STEAM) courses are a popular trend in international education than can help inculcate creativity in students. Although STEAM courses have been widely promoted in China, they are generally unsustainable because they are merely imitations of European and American courses and lack Chinese humanistic factors; a close integration between disciplinary ideas and thinking levels is also lacking. C-STEAM, which is designed to pass down China’s culture, is a form of STEAM education with local Chinese characteristics that are focused on integrating interdisciplinary knowledge with the thought process oriented toward cultural heritage. Methods In this study, an innovative higher vocational college course with C-STEAM interdisciplinary principles was constructed, with art and design as the framework, and with the integration of Chinese local culture. Semi-structured interviews were conducted to sample 12 learners from a total of 90 students in the experimental class of the C-STEAM course. The study aimed to provide a deeper understanding of the effectiveness of taking a Packaging Design course combined with C-STEAM from multiple perspectives. After the interviews, based on the BAO model, coding statistics and thematic analysis were conducted to understand the learners’ beliefs, actions, and outcomes after taking the course, and their plans for acquiring C-STEAM interdisciplinary knowledge and learning Chinese local culture. Results The integration of the Shangshan culture (上山文化) into the Packaging Design course proved the importance and significance of adding C-STEAM to the art design course, which helped us understand the specific feelings of students after completing the course and gain a deeper understanding of the changes in their knowledge and skills and their learning effects. Discussion Integrating C-STEAM education into courses related to art and design is highly warranted to encourage students to apply their interdisciplinary knowledge to artistic exploration and creation. Moreover, to effectively develop a curriculum system with local characteristics, teachers should provide more opportunities for students to explore and learn C-STEAM in the future, and integrate multiple elements into their teaching. In general, a cultural perspective-based interdisciplinary education helps facilitate the creative transformation of traditional Chinese culture.